Sociodemographic, clinical, and therapeutic characteristics of patients with Visceral Leishmaniasis in southwestern Maranhão, Brazil (Revista Contexto & Saúde, 2025)
Introduction: Human Visceral Leishmaniasis (HVL) remains a significant public health issue in Brazil, with an estimated 400,000 cases and 20,000 to 40,000 deaths annually. Over the past three decades, the disease has rapidly expanded, primarily due to urbanization, resulting in a shift in its epidemiological profile toward urban centers. Despite this trend, regional data on the sociodemographic, clinical, and therapeutic characteristics of HVL cases remain limited, particularly in Maranhão. This study aimed to fill this gap by characterizing HVL cases in the southwestern region of the state. Methods: A descriptive, cross-sectional, and retrospective study was conducted using data from the Notifiable Diseases Information System (SINAN). HVL cases reported from 2009 to 2018 across sixteen municipalities within the macro-region of the 10th Health Regional Management Unit of Maranhão were analyzed. Results: A total of 623 HVL cases were recorded, with 95% classified as new cases. The incidence rate was 1.15 cases per 100,000 inhabitants over the ten-year period. Most cases involved male children from urban areas, revealing key sociodemographic patterns. Conclusions: The study confirmed the region's high endemicity and the predominance of new HVL cases. These findings highlight the need for enhanced surveillance efforts and underscore the clinical significance of early diagnosis.
Keywords: Visceral Leishmaniasis; Epidemiology; Clinical Profile; Therapeutic Profile; Prevention and Control